Analisis Kinerja Keuangan Dalam Menilai Pertumbuhan Laba Pada Perusahaan Subsektor Semen Yang Terdaftar Di Bursa Efek Indonesia - Nasrun Julyarman (LP2M IBK Nitro, 2022)
This study aims to analyze financial performance in assessing profit growth in cement sub-sector companies listed on the Indonesia Stock Exchange. The method used in this study is the analysis of financial ratios (liquidity ratio, leverage ratio, activity ratio, profitability ratio) and profit growth with the research sample using a purposive sampling technique for the specified conditional sample 1) the company has published financial statements during the study period and 2) the company has financial data its profitability decreased during the study period. The results of the study showed that it had poor profit growth because its profit growth decreased every year. Based on the results of the study.